The (almost) unknown Italian naturalist Raffaello Bellini (1874–1930): biography, malacological publications, and status of his recent molluscan taxa - Fasulo, Giuseppe; Duraccio, Sergio; Federico, Antonio; Crocetta, Fabio (Zootaxa, 2019)
Raffaello Bellini (1874–1930) was an almost unknown Italian naturalist who produced a wide scientific literature. He followed the “Golden Age” of the Neapolitan Malacological School and his malacological papers were particularly related to Italy, focusing on marine, freshwater, fossil, and terrestrial species. We hereby highlight and summarize Raffaello Bellini’s biography and malacological work, and revise the status of recent molluscan taxa described by him. Our bibliographic research revealed that from 1897 to 1929 Bellini published 41 papers dealing with malacology and altogether instituted 46 molluscan nominal taxa, 17 of which are based on fossil samples and 29 on recent samples. Within the latter group, 24 (13 marine, nine terrestrial, and two freshwater) taxa are potentially available, whilst five (two marine and three terrestrial) are nomina nuda. Among these 24 taxa, 13 are available, ten have infrasubspecific rank and thus are not available, and one is permanently invalid. Among available binomial names, seven are junior synonyms of valid taxa and six are nomina dubia. Gibbula umbilicaris var. acherusiae Bellini, 1903 is here considered a junior synonym of Gibbula ardens (Salis Marschlins, 1793) for the first time. Finally, three recent marine molluscan taxa were named after Raffaello Bellini. However, none of these species proved to be valid. The present paper sheds light on the work done by the latest of the “early” authors of the Neapolitan Malacological School and contributes to nomenclature and taxonomy of Recent European molluscan taxa.